An evaluation of the Phragmites australis reed use by communities neighbouring the Tembe Elephant Park, Maputaland, KwaZulu-Natal, South Africa - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.